2016
DOI: 10.1063/1.4967768
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electrostatic solitary pulses in magnetized quantum plasma with relative density effects of spin-up and spin-down electrons

Abstract: A separated spin evolution quantum hydrodynamics model is employed to study low frequency electrostatic waves in plasmas having inertia-less degenerate electrons with spin-up ne↑ and spin-down ne↓ states and inertial classical ions. A two-dimensional plasma geometry is assumed having a uniform magnetic field, directed along the z-axis, i.e., B=B0ẑ. A Zakharov-Kuznetsov (ZK) type equation is derived for the electrostatic potential via the Reductive Perturbation Technique. The parametric role of the spin densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In the limiting case, when coefficient C vanishes in (38) of [20] and in (29) of [21], one can get the KdV equation, which agrees with (30) (for C = 0) in the present investigation.…”
Section: Derivation Of the Kdv Equationsupporting
confidence: 88%
See 1 more Smart Citation
“…In the limiting case, when coefficient C vanishes in (38) of [20] and in (29) of [21], one can get the KdV equation, which agrees with (30) (for C = 0) in the present investigation.…”
Section: Derivation Of the Kdv Equationsupporting
confidence: 88%
“…Owing to the presence of spin-up and spin-down electrons in a degenerate quantum plasma, some investigations focusing on the study of solitary and shock waves have been reported. Ahmad et al [20] investigated the lowfrequency electrostatic waves in plasmas having inertialess degenerate electrons by employing the separated spin evolution QHD model. The pulse stability analysis was carried out, and it was also found that spin polarisation significantly affects the amplitude and width of the solitary waves.…”
Section: Introductionmentioning
confidence: 99%
“…A significant influence of the spin polarization on the amplitude and width of the acoustic dark soliton (presented in terms of the scalar potential of the electromagnetic field) is found for the magnetized electron-ion plasmas in Ref. [23]. It is demonstrated that the increase of the spin polarization leads to the increase of the module of the soliton amplitude.…”
Section: Introductionmentioning
confidence: 94%
“…Majority of application of the separate spin evolution quantum hydrodynamics (SSE-QHDs) is related to the spin-electron acoustic waves (SEAWs). However, there are papers devoted to the influence of the separate spin evolution and the spin polarized Fermi pressure on the following phenomena: Raman three-wave interaction for the pump wave (O-mode), sideband Shear Alfven wave, and the electron * Electronic address: andreevpa@physics.msu.ru plasma perturbations [33], and non-linear propagation of ion-acoustic waves [34].…”
Section: Introductionmentioning
confidence: 99%